APB online workshop series: English for university professionals / Isma Noornisa Ismail - Ismail, Isma Noornisa (Academy of Language Studies, 2022)
When you hear the term ‘small talk’, many would wonder of its significance. Is it really important? Why would we even bother learning this skill? Well, despite being ‘small’, this social skill is essential as it enables effective networking, forms positive impressions, as well as acts as a saviour in any awkward conversation. In recognition of its importance in professional career development, APB had organised the Online Workshop Series, and the second series of this workshop focused solely on ‘Engaging in Meaningful Small Talks’. This two-hour workshop was held on 17th December 2021, via Google Meet and was facilitated by Prof. Madya Dr Rushita Ismail, Mr. Lim Teck Heng, Mr. Rasaya Marimuthu, Pn. Hanani Ahmad Zubir, Pn. Muriatul Khusmah Musa, and Dr Isma Noornisa Ismail